L05 Summary of carer's views of the decision to insert a percutaneous endoscopic gastrostomy (PEG) feeding tube. (29th August 2012) - Fillingham, K; Quarrell, O; Rickards, H; O'Donovan, K
Abstract : In the later stages of HD, Percutaneous Endoscopic Gastrostomy (PEG) feeding is considered an alternative or supplement to oral feeding. As part of a wider study, qualitative analysis was used on data from semi structured interviews on the decision making process for PEG feeding tubes. This was carried out from a sample of 23 carers (7 from prospective patients and 16 from retrospective patients) during 2010–2011 for patients who had PEG feeding tubes. The investigator identified three main themes from this analysis; The need for information; Why the decision regarding the PEG feeding tube needed to be made, how the decision was made and the actual procedure of the PEG insertion. Three families identified the information provided was clear and adequate. Three families were not satisfied with this information. One family requested more clinical meetings to enable the decision. Provision of Time; to enable the decision to be made. Three families commented positively on the adequate provision of time. Professional Support; to enable the decision to be made. Four families expressed receiving adequate support. Two families identified a lack of support. In summary, eight carers expressed no particular opinion of the decision making process. Twelve of the 20 carers reported a positive experience and three carers expressed a negative experience. The study could form part of the basis for the production of best practice guidelines and contribute towards decision making models.